Analysis of DNA haplotypes suggests a genetic predisposition to trisomy 21 associated with DNA sequences on chromosome 21. - Antonarakis, S E (1985)
To test the hypothesis that there is a genetic predisposition to nondisjunction and trisomy 21 associated with DNA sequences on chromosome 21, we used DNA polymorphism haplotypes for chromosomes 21 to examine the distribution of different chromosomes 21 in Down syndrome and control families from the same ethnic group. The chromosomes 21 from 20 Greek families with a Down syndrome child and 27 control Greek families have been examined for DNA polymorphism haplotypes by using four common polymorphic sites adjacent to two closely linked single-copy DNA sequences (namely pW228C and pW236B), which map somewhere near the proximal long arm of chromosome 21. Three haplotypes, +, +---, and - with respective frequencies of 43/108, 24/108, and 23/108, account for the majority of chromosomes 21 in the control families. However, haplotype - was found to be much more commonly associated with chromosomes 21 that underwent nondisjunction in the Down syndrome families (frequency of 21/50; X2 for the two distributions is 9.550; P = 0.023; degrees of freedom, 3). The two populations (control and trisomic families) did not differ in the distribution of haplotypes for two DNA polymorphisms on chromosome 17. The data from this initial study suggest that the chromosome 21, which is marked in Greeks with haplotype - for the four above described polymorphic sites, is found more commonly in chromosomes that participate in nondisjunction than in controls. We propose an increased tendency for nondisjunction due to DNA sequences associated with a subset of chromosomes 21 bearing this haplotype.